Hasil Perikanan : Manfaat dan Keamanannya Serta Implikasinya Pada Kesehatan ; Tinjauan dari Sisi Teknologi Pengolahan dan Lingkungan - Suwedo Hadiwiyoto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1997)
The benefits of fish and fish products are their high nutrition value, rich of minerals, vitamine A and D, and as a sources of n-3 polyunsaturated fatty acids. Consuming of fish products may ameliarate desorders involving thrombosis, blood pressure, arthritis, asthma, artherosclerosis, tumor growth, etc. However, uncontrolled handling and processing may result in negative impacts to health. Polycyclic aromatic hydrocarbon and aromatic hydrocarbon amine generally found in smoked fish are carcinogenic. Oxidation of lipid compounds may be enhanced during processing and storage and produce unhealthy substances. Some bacteris produce histamine from free histidine whereas growth of fungi produce mycotoxins could be found in dried fish products. Heavy metal and pestiside contained in fish are due to environmental contamination. Fish may also be contaminated by toxic algae and parasites such as tapeworms, flukes, and roundworms.